PENGARUH KREATIVITAS GURU TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI - Armalena Lena; Sutri - Lesti (al-Iltizam: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study was to see how the influence of teacher creativity on students' interest in learning in Islamic religious education subjects at Madrasah Aliyah Plus Ulil Albab Inuman, Kuantan Singingi Regency, Riau Province. The method used in this research is descriptive quantitative method with a pospositivist approach (reality or facts). This research was conducted at Madrasah Aliyah Plus Ulil Albab Inuman, Strengthening Singingi Regency, Riau Province, which is located at Jl. Inuman Market Circle, Kuantan Singingi Regency, Riau Province. This study is a population study because the respondents in the study amounted to 63 people, which is the total number of students at the Aliyah level. Data collection techniques were carried out by distributing questionnaires and documentation as well as data analysis with simple linear regression. The results of this study indicate that the creativity of teachers at Madrasah Aliyah Plus Ulil Albab belongs to the poor category. This is evidenced by the mean = 54.62 and the interval is 54 - 58 and students' interest in learning in Islamic religious education subjects is included in the low category with mean = 53.89 and the interval is at 47 - 53 as well as the influence of teacher creativity on students' interest in learning in these subjects. Islamic religious education lessons at Madrasah Aliyah Plus Ulil Albab show that there is an influence of teacher creativity on student interest in learning by referring to the value of Fcount = 43,406 at the level of sig 0.000 and sig < (0.000 < 0.05) which when presented is 41.6% and the remaining 58.4% is influenced by other variables not discussed in this study.Tujuan penelitian ini adalah untuk melihat bagaimana pengaruh kreativtas guru terhadap minat belajar siswa pada mata pelajaran pendidikan agama Islam di Madrasah Aliyah Plus Ulil Albab Inuman Kabupaten Kuantan Singingi Provinsi Riau. Metode yang dipakai pada penelitian ini adalah metode kuantitatif deskriptif dengan pendekatan pospositivist (realita atau fakta). Penelitian ini dilakukan di Madrasah Aliyah Plus Ulil Albab Inuman Kabupaten Kuatan Singingi Provinsi Riau yang beralamat di Jalan Lingkar Pasar Inuman Kabupaten Kuantan Singingi Provinsi Riau. Penelitian ini merupakan penelitian populasi karena responden dalam penelitian berjumlah 63 orang yang merupakan jumlah keseluruhan siswa pada tingkat Aliyah. Teknik pengumpulan data dilakukan dengan penyebaran angket dan dokumentasi serta analisis data dengan regresi linear sederhana. Hasil dari penelitian ini menunjukkan bahwa kreativitas guru di Madrasah Aliyah Plus Ulil Albab tergolong pada kategori kurang baik. Ini dibuktikan dengan mean = 54,62 dan interval 54 – 58 dan minat belajar siswa pada mata pelajaran pendidikan agama Islam termasuk pada kategori rendah dengan mean = 53,89  dan interval berada pada 47 – 53 serta pengaruh kreativitas guru terhadap minat belajar siswa pada mata pelajaran pendidikan agama Islam di Madrasah Aliyah Plus Ulil Albab menunjukkan adanya pengaruh dari kreativitas guru terhadap minat belajar siswa dengan berpedoman kepada nilai Fhitung = 43,406 pada taraf sig 0,000 dan sig < α (0,000 < 0,05) yang apabila dipersentasekan  sebesar 41,6% dan sisanya 58,4% dipengaruhi oleh variabel lain yang tidak dibahas dalam penelitian ini.